Forgiveness Pada Hubungan Romantis Ditinjau Dari Kepercayaan Interpersonal Dan Agreeableness Mahasiswa - Salsabila, Mustamira Sofa; Chaerani, Martha (ANFUSINA: Journal of Psychology, 2021)
Romantic relationships in late adolescence will last longer also have stronger and stable emotional bonds as in adult phase. Sometimes in a romantic relationship will have conflict. Interpersonal trust in partners is a factor in romantic relationships in resolving conflicts with forgiveness. Besides, agreeableness of the partner’s personality can also be a factor in resolving conflicts with forgiveness. This study has three objectives, there are to find out correlation between interpersonal trust and agreeableness with forgiveness of romantic relationships, to find out correlation between interpersonal trust with forgiveness of romantic relationships, and to find out correlation between agreeableness with forgiveness of romantic relationships. The method used in this research is a quantitative method using 3 psychological scales, there were the TRIM-18 scale, the Trust scale, and the BFI scale by taking the agreeableness dimension. The sampling technique used purposive sampling with a total sample of 91 respondents. The sample of this study were students of Ushuluddin and religion study Faculty in major Islamic Psychology at UIN Raden Intan Lampung in 2017, 2018 and 2019 generations who were in a romantic relationship for 6 months or more and had conflicts experienced. The results obtained from this study indicate that there was a significant positive correlation between interpersonal trust and agreeableness with forgiveness, with R=0,433 and the value of F=10,159 significant p=0,000 (p≤ 0,01) with a contributions by 18,8%.  Based on the results of data analysis, it was obtained that interpersonal trust also had positive correlation to forgiveness (r= 0,289 dan p = 0,005 (p < 0,01)) with effective contributions by 3,9%. Besides, agreeableness also had significant positive correlation to forgiveness and has more contributions than other independent variable in this study (r=0,415 dan p=0,000 (p≤0,01)) with effective contributions by 14,8%.Keywords: forgiveness, interpersonal trust, agreeableness, romantic relationship